Effect of different aerogel percentage coating on thermal insulating performance - Abu Talib, Abd Rahim; Harmin, Mohammad Yazdi; Saadon, Syamimi; Gires, Ezanee; Mohd Zulkeple, Muhammad Fitri; Muhamud, Rahimi L.; Bastan, Javier (Tamkang University Press, 2024)
This paper discusses the effect of employing different percentage of aerogel powder in paint solution for thermal insulating performance. This issue has led to the development of a fresh, inventive solution that has the ability to insulate against heat, allowing for a reduction in material thickness during construction. Due to its characteristics, aerogel is a great addition to coatings that are lightweight and thermally insulating. As an additive for the created thermal coating in the current investigation, different volume of aerogel ranging from 1% to 5% have been blended. The enhanced coating was then put to an ISO-NUD microporous panel in order to observe the effects of the aerogel addition. The testing results show that employing aerogel-infused coatings or paint can help an ISO-NUD microporous panel function better as a thermal insulator based on the temperature difference between the panel’s front and back surfaces. It became evident that a higher percentage of aerogel provide the better insulation. With the additional of 5% of aerogel, there was about 7% of thermal insulation enhancement that was recorded follow by the 5% of enhancement by addition of the 4% of aerogel. The additional of 3% and 2% of aerogel share almost similar level of enhancement which are about 3%. While the additional of 1% of aerogel seen unable to show significant enhancement compared to the normal paint without aerogel been infused